Kebimbangan berkomunikasi dengan pasangan dan kepuasan perkahwinan dalam kalangan individu Melayu yang berkahwin di Lembah Klang, Malaysia - Suzana Mohd Hoesni; Jamiah Manap; Siti Marziah Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2020)
Communication within marriage has been reported as one of the most important factors that contribute to marital satisfaction. However, not many studies have investigated the psychological dynamics of communication among married individuals. Thus, the aim of this study is to identify the relationship between spouse communication apprehension and marital satisfaction. This study is partly from a larger study that investigates psychological aspects of marital satisfaction. A number of 578 Malay married respondents (male=256, female=322) from Lembah Klang volunteered to participate in this study. Questionnaires consisted of questions relating to background information of respondents, spouse communication apprehension and marital satisfaction was distributed to the respondents. Completed questionnaires were collected for analysis. Overall, Pearson Correlation analysis results show that there were a significant negative relationship (r= -.485**, k<0.01) between spouse communication apprehension and marital satisfaction. This study indicates that communication apprehension that happens with spouse is an important factor and needed attention should be taken when studying psychological aspects among married individuals. Findings pose implication to researchers and helping professionals such as counselors, therapists and social workers working with married individuals and couples.